Factorization of reciprocal Hilbert port operators - Gnavi, G. (1986)
Factorization of J-biexpansive operator-valued functions on an infinite-dimensional Hilbert space is performed, to extract terms with an arbitrary number of poles of first order on the left and right half planes. Special emphasis is given to the case of reciprocal poles, which has an application to the synthesis of reciprocal passive linear systems as an extension of the classical synthesis of reciprocal n-ports by factor decomposition. © 1986.